Expression of Chitinases and Glucanases in Oil Palm in Response to Ganoderma and Trichoderma Treatments - Yeoh, Keat Ai (2011)
Cell wall degrading enzymes (CWDEs) such as chitinases and glucanases are produced by plants during the infection of pathogens as part of their defense mechanism. In this study, the full length complementary DNA (cDNA) sequences encoding two chitinases (EgChit3-1 and EgChit5-1) and one (EgGlc5-2) glucanase from the oil palm root have been isolated by Rapid Amplification of cDNA Ends – Polymerase Chain Reaction (RACE-PCR). Meanwhile the 5’- terminal cDNA sequence encoding a chitinase (EgChit1-1) was successfully isolated. Sequence analysis was performed on the three full-length cDNA sequences obtained from this study and two full-length cDNA sequences encoding glucanases (EgGlc1-1 and EgGlc5-1) obtained from the expressed sequence tags (ESTs) of oil palm root cDNA library. Analyses of the cDNA sequences revealed that EgGlc1-1 is related to the glycosyl hydrolase (GH) family 3 while EgGlc5-1 and EgGlc5-2 are related to the GH family 17. EgChit1-1 was categorized in the GH family 19 whereas EgChit3-1 and EgChit5-1 are related to the GH family 18. Real time reverse transcription polymerase chain reaction (RT-PCR) was performed to detect the transcript levels of the isolated glucanases and chitinases using oil palm seedlings treated with Ganoderma boninense PER71, Trichoderma harzianum T32 singly and in a combination of Ganoderma and Trichoderma at 3, 6 and 12 weeks post infection (wpi). Lesions caused by Ganoderma infection were only observed at 6 wpi and 12 wpi in Ganoderma-treated seedlings. The Trichoderma colony forming unit (CFU) estimation in Ganoderma-Trichoderma- and Trichoderma-treated seedlings increased gradually from 3-12 wpi. The expression of EgGlc1-1 was induced by Trichoderma in Trichoderma-treated seedlings at 3, 6 and 12 wpi. The expression of EgGlc5-1 and EgGlc5-2 was elevated in the roots of control seedlings while suppressed treated seedlings at 3, 6 and 12 wpi. The transcript encoding EgChit1-1 increased in respond to Ganoderma infection at early stage (3 wpi). The transcript of EgChit3-1 and EgChit5-1 were increased at later stages of infection in roots of Ganoderma- and Trichoderma-treated seedlings. The findings of this study provide an insight to the gene expression of a few glucanases and chitinases during colonization of Ganoderma and Trichoderma on oil palm seedlings. Not all glucanases and chitinases in this study played a role in oil palm defense. Different glucanases and chitinases were regulated differently in oil palm seedlings when they were exposed to Ganoderma, Trichoderma singly and in a combination of Ganoderma-Trichoderma.